Non-linear cosmological perturbations for coupled dark energy - Tüdes, Bilal; Amendola, Luca (Journal of cosmology and astroparticle physics, 2025)
We derive the one-loop perturbation kernels for a minimal modified gravity model in which dark energy is coupled to dark matter via a constant coupling. We derive the time-dependent kernels via analytical and numerical solutions and provide accurate fitting functions. These kernels can be directly employed to test for modified gravity in forthcoming large-scale surveys.